Treatment patterns and risk factor control in patients with and without metabolic syndrome in cardiac rehabilitation - Gitt, Anselm Kai; Karoff, Marthin; Horack, Martin (Vascular health and risk management, 2012)
Aim Metabolic syndrome (MetS) is a clustering of factors that are associated with increased cardiovascular risk. We aimed to investigate the proportion of patients with MetS in patients undergoing cardiac rehabilitation (CR), and to describe differences between patients with MetS compared to those without MetS with regard to (1) patient characteristics including demographics, risk factors, and comorbidities, (2) risk factor management including drug treatment, and (3) control status of risk factors at entry to CR and discharge from CR. Methods Post-hoc analysis of data from 27,904 inpatients (Transparency Registry to Objectify Guideline-Oriented Risk Factor Management registry) that underwent a CR period of about 3 weeks were analyzed descriptively in total and compared by their MetS status. Results In the total cohort, mean age was 64.3 years, (71.7% male), with no major differences between groups. Patients had been referred after a ST elevation of myocardial infarction event in 41.1% of cases, non-ST elevation of myocardial infarction in 21.8%, or angina pectoris in 16.7%. They had received a percutaneous coronary intervention in 55.1% and bypass surgery (coronary artery bypass graft) in 39.5%. Patients with MetS (n = 15,819) compared to those without MetS (n = 12,085) were less frequently males, and in terms of cardiac interventions, more often received coronary artery bypass surgery. Overall, statin use increased from 79.9% at entry to 95.0% at discharge (MetS: 79.7% to 95.2%). Patients with MetS compared to those without MetS received angiotensin converting enzyme inhibitors, angiotensin receptor blockers, oral antidiabetics, and insulin at entry and discharge more frequently, and less frequently clopidogrel and aspirin/clopidogrel combinations. Mean blood pressure was within the normal range at discharge, and did not differ substantially between groups (124/73 versus 120/72 mmHg). Overall, between entry and discharge, levels of total cholesterol, low density lipoprotein cholesterol, and triglycerides were substantially lowered, in particular in MetS patients. Thus, control rates of lipid parameters improved substantially, with the exception of high density lipoprotein cholesterol. Low density lipoprotein cholesterol rates <100 mg/dL increased from 38.7% at entry to 73.8% at discharge (MetS: from 39.4% to 74.6%) and triglycerides control rates (<150 mg/dL) from 58.1% to 70.4% (MetS: 43.7% to 62.2%). Physical fitness on exercise testing improved substantially in both groups. Conclusion Patients with and without MetS benefited substantially from the participation in CR, as their lipid profile, blood pressure, and physical fitness improved. Treatment effects were similar in the two groups.